2020
DOI: 10.1103/physrevlett.125.188001
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Origin of Nonlocal Rheology in Dense Granular Materials

Abstract: We study the microscopic origin of nonlocality in dense granular media. Discrete element simulations reveal that macroscopic shear results from a balance between microscopic elementary rearrangements occurring in opposite directions. The effective macroscopic fluidity of the material is controlled by these velocity fluctuations, which are responsible for nonlocal effects in quasistatic regions. We define a new micromechanically based unified constitutive law describing both quasistatic and inertial regimes, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…We further showed that in the quasi-static shearing regime (V ≲ 1 m/s, for a normal stress of 5 MPa), the fluctuating kinetic energy becomes nearly constant, which would suggest a nearly constant magnitude of the direct effect, consistent with most laboratory rock and gouge friction experiments (Bhattacharya et al, 2015;Kilgore et al, 1993). A nearly constant value of effective granular temperature in the quasi-static regime has also been previously reported in experimental granular physics studies (Corwin et al, 2005;Song et al, 2005), although more recent studies of granular systems with different loading geometries (i.e., other than tabular gouge layers between parallel plates) shows that this behavior could be influenced by localized deformation close to driving boundaries (Gaume et al, 2020;Kim & Kamrin, 2020;P. Richard et al, 2020).…”
Section: Energetics Of Granular Slide-holdssupporting
confidence: 86%
“…We further showed that in the quasi-static shearing regime (V ≲ 1 m/s, for a normal stress of 5 MPa), the fluctuating kinetic energy becomes nearly constant, which would suggest a nearly constant magnitude of the direct effect, consistent with most laboratory rock and gouge friction experiments (Bhattacharya et al, 2015;Kilgore et al, 1993). A nearly constant value of effective granular temperature in the quasi-static regime has also been previously reported in experimental granular physics studies (Corwin et al, 2005;Song et al, 2005), although more recent studies of granular systems with different loading geometries (i.e., other than tabular gouge layers between parallel plates) shows that this behavior could be influenced by localized deformation close to driving boundaries (Gaume et al, 2020;Kim & Kamrin, 2020;P. Richard et al, 2020).…”
Section: Energetics Of Granular Slide-holdssupporting
confidence: 86%
“…Also, as shown recently in ref. [18] and [19], the granular temperature also plays a key role in determining the rheology of such systems and hence, along with µ and I, the granular temperature also needs to be considered,especially for the region where I > 0.03. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observed difference hints the effect of terrain irregularity on the flow regime transition. Indeed, a more complex terrain can induce significant local velocity variations, leading to a different rheology (Gaume et al 2020 ). The avalanche simulated in case IV is apparently a plug flow as identified in the 2D modeling, which shares similarity with real avalanches in the warm plug regime.…”
Section: Discussionmentioning
confidence: 99%